2008
DOI: 10.1258/ijsa.2008.008153
|View full text |Cite
|
Sign up to set email alerts
|

Unlinked anonymous HIV prevalence among New Zealand sexual health clinic attenders: 2005–2006

Abstract: This unlinked anonymous study aimed at determining the prevalence of HIV among sexual health clinic attenders having blood samples taken for syphilis and/or hepatitis B serology in six major New Zealand cities over a 12-month period in 2005-2006. Overall, seroprevalence was five per 1000 (47/9439). Among men who have sex with men (MSM), the overall prevalence and that of previously undiagnosed HIV were 44.1 and 20.1 per 1000, respectively. In heterosexual men, the overall prevalence was 1.2 per 1000 and in wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 6 publications
2
20
0
Order By: Relevance
“…In a study [34] In cross-sectional studies from Southeast Asia, HIV prevalence in MSM ranged from 0.7 to 8.7% in Cambodia [40], from zero to 7.8% in Vietnam [41,42] and from 17.3 to 30.8% in Thailand [43,44] and was 5.6% in Lao PDR [45]. In Myanmar, 29.3% of MSM were found to be HIVinfected in two study sites in 2007 [46].…”
Section: North Americamentioning
confidence: 99%
“…In a study [34] In cross-sectional studies from Southeast Asia, HIV prevalence in MSM ranged from 0.7 to 8.7% in Cambodia [40], from zero to 7.8% in Vietnam [41,42] and from 17.3 to 30.8% in Thailand [43,44] and was 5.6% in Lao PDR [45]. In Myanmar, 29.3% of MSM were found to be HIVinfected in two study sites in 2007 [46].…”
Section: North Americamentioning
confidence: 99%
“…21,22 Much will then depend on the relative contribution to annual HIV transmissions of individuals in different stages of HIV disease, and with diagnosed or undiagnosed infection. [23][24][25] To better elucidate which factors help explain the increase in HIV diagnoses among MSM in New Zealand, further consideration should be given to disaggregated behavioural surveillance data on trends in condom use and HIV testing, 3 repeat cross-sectional research on MSM living with diagnosed HIV, 26 anonymous HIV seroprevalence studies 1 and HIV prevention programs. 27 Current gaps in research and surveillance that could shed light on drivers of the increase also need to be identified and prioritised, particularly research on sexual networks, STI surveillance for MSM and community HIV prevalence studies.…”
Section: Increase In Hiv Diagnoses Among Msm In Nzmentioning
confidence: 99%
“…1 Anonymous unlinked seroprevalence studies in 1991-92 and 2005-06 revealed that 4.4% of MSM attending sexual health clinics were HIVpositive, 1,2 a figure which is likely to overestimate HIV prevalence among all MSM, since this subgroup contains a high proportion of men presenting with a sexually transmissible infection (STI). Accordingly, fewer than 5% of MSM recruited at gay community venues and events in Auckland reported having received an HIV-positive diagnosis, 3 and an analysis of national routine surveillance data estimated that diagnosed HIV prevalence was between 1.5% and 5% of MSM in 2009.…”
Section: Introductionmentioning
confidence: 99%
“…In New Zealand, while gay, bisexual and other men who have sex with men (MSM) face an overwhelmingly higher burden of HIV than heterosexual men and women,1 less is known about how they are affected by other sexually transmitted infections (STIs). Routine STI surveillance is based on conditions seen at sexual health clinics (SHCs) and laboratory diagnosed Chlamydia trachomatis and Neisseria gonorrhoeae ; however, neither of these sources report the numbers with same-sex behaviour.…”
Section: Introductionmentioning
confidence: 99%